PEMANFAATAN PANAS TERBUANG BOILER UNTUK PENCETAKAN KERUPUK LEPIT - Irna Sari Maulani; Syamsuri, Heris; Abidin, Zenal (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2023)
Lepit crackers are one of the types of crackers in Indonesia. Made from tapioca flour and a mixture of other ingredients, this food is very popular with all people, of course the taste is very unique. In Cipaku Subdistrict, Ciamis Regency, the place where the cracker cracker is made, precisely at the Sumber Usaha factory, is still manual by hand. This of course reduces the productivity of the production process. This research is targeted to produce a semi-automatic based cracker machine by utilizing steam heat from the boiler. By having a working principle of utilizing the rotation of an electric motor as a source of automatic propulsion of the tool. This study aims to increase the productivity of the cracker production process at the Sumber Usaha Cipaku factory. This research includes several stages including data collection, design analysis, preparation of tools and materials, the process of making tools, then testing whether the tools work successfully. The target of this research is the success of the manufacturing process for making crackers and can help increase the productivity of the Sumber Usaha factory. Keywords: Lepit cracker printer, Electric motor.